The sorption of organic compound in soils - Muhammad Aizuddin , Ramly (2013)
Nowadays, world is facing one of the most critical problem which is water scarcity. These become a factor to the usage of wastewater to the wastewater reuse application. Globally wastewater is used as irrigation water especially for crops in agriculture activities. The advantages of reuse of wastewater in agriculture such as conserves water, reduces pollution of rivers due to the wastewater treatment plan discharged and other surface water, conserves nutrients and reducing the need of artificial fertilizer, increases crop yields and provides a reliable water supply to farmers. Although the function of wastewater treatment plant has been well noted such as remove odor, bad tastes and settable solids inside the wastewater but there is still some organic compounds that be able to escape from the treatment process thus presence in the final effluent. One of the organic compounds that have been reported is polycyclic aromatic hydrocarbons (PAHs). The presence of these organic compounds in soil and water are mostly caused by the reuse of wastewater as irrigation water. Soil play important role in the distribution of PAHs to environment. Soil has properties to behave as a dual sorbent. Mineral matter of soil sorbs contaminant by adsorption while soil organic matter sorbs the contaminant by partitioning. In this study, soil samples were taken from top soil from agriculture soils and the contaminant was Benzo(a)pyrene. In sorption batch experiment, soil- water partition coefficient (Kd) and soil-water partition coefficient normalized to organic carbon (Koc) determination were conducted in order to determine the sorption process of PAHs in these soils. The result shows the highest sorption coefficient (kd) exhibit in Top soil 3 while Top soil 1 exhibit the lowest. Therefore Top soil 3 exhibit stronger bond with Benzo(a)pyrene. Organic matter plays a dominant role in partitioning process of Benzo(a)pyrene in all soil. As the organic content increases, the sorption coefficient also increases for all soil.